Two small thermodynamically stable organic dications - YUMAK YAHŞİ, AYŞE; YAVUZ, İLHAN; ALTUN, ZİKRİ (ELSEVIER, 2010)
Small multiply charged species may be long-lived without the benefit of stabilization by a medium, primarily owing to the Coulomb barrier that impedes both formation and dissociation of the systems. We extend the category of small organic dicationic structures that may possess thermodynamic stability to include derivatives of cyanoacetylene. The linear dication HCCCNH(2+) and its isomer HCCNCH(+2) are characterized in detail; according to CCSD(T)/6-31G(d,p)//MCSCF(7,13)/6-31G(d,p) estimates, HCCCNH(2+) is thermodynamically stable by 2.8 eV and the barrier to colinear dissociation is ca 4.1 eV. The isomer HCCNCH(2+) is thermodynamically stable by about 2.1 eV and the barrier to colinear dissociation is ca 4.5 eV. Preparation of these systems by charge stripping of the predecessor H2C3N monocation may be feasible. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Organic cations; Interstellar molecules; Density functional calculations; Coupled cluster calculations; COUPLED-CLUSTER METHODS; MOLECULAR DICATIONS; STATE; ANTIAROMATICITY; FLUORENYLIDENES; OXIDATION; ENERGIES; CATIONS; HCCNC; C2H2